Characteristics of the Lodz Polish Press Market: Bibliographic Draft - Mikosz, Joanna (Media - Culture - Social Communication, 2019)
This article was written to present the contemporary Lodz press market. The publication consists of three parts. The first part discusses the press market formation process in Lodz until 1989; the author performed the characteristics and typology of titles appearing that time. Next, the effects of press transformations after the end of communism are presented and show its impact on the substantive content of this medium. In the next part of the article, the contemporary Lodz press impact criteria and their functions are distinguished. In addition, the author presents the typology and characteristics of press titles currently published in the city.